A large, single center investigation of the immunogenetic factors affecting liver transplantation - Doran, Trevor; Geczy, A.F.; Painter, D.; McCaughan, G.; Sheil, A.G.; Süsal, Caner; Opelz, Gerhard (Transplantation, 2000)
BACKGROUND: Reports on the relevance of immunogenetic factors in liver transplantation are often conflicting or inconclusive. We have, therefore, investigated a range of factors that may underlie liver graft survival. METHODS: The influences of HLA, flow cytometric, and enhanced cytotoxic crossmatching and immunoglobulin (Ig)A levels on graft survival, and acute and chronic rejection were investigated for a single center involving 446 patients over 13 years. RESULTS: The effect of HLA mismatching on graft survival was significant (P<10(-2)) and was reversed in recipients with autoimmune diseases (P<0.5x10(-2)), whereas the effect of HLA mismatches on the level of acute rejection was detrimental in all recipients. There was a significant effect of a positive cytotoxic crossmatch on 3-month (P<10(-5)) and 1-year (P<10(-4)) graft survival, and an additional effect of the flow cytometric crossmatch was seen for chronic rejection (P<10(-2)) and acute rejection (P<10(-2)). Recipients with HLA-A1,B8,DRB1*0301 had higher levels of acute rejection (P<0.5x10(-2)), and recipients who received an ABO compatible-nonidentical transplant have a significantly higher risk (P<10(-2)) of developing chronic rejection. Finally, the beneficial effect of high serum IgA and, specifically, IgA anti Fab, seen in renal transplants was not evident in liver transplants, and in fact the opposite may be true, at least for acute rejection (P<0.5x10(-2)). CONCLUSIONS: By separating the recipients with autoimmune disease from other patients and by including acute and chronic rejection as outcome parameters, we have used the power of a large single-centre study to delineate the significance of some of the important immunogenetic factors involved in liver transplantation.
Gesehen am 19.02.2021